Physiological responses of hydroponically-grown Japanese mint under nutrient deficiency - Chananchida Janpen (2020)
Copyright 2019 Janpen et al. This research aims to determine growth and deficiency patterns as well as antioxidative potentials of Japanese mint (Mentha arvensis) hydroponically grown under limited macronutrients and micronutrients. The experiment was conducted for 60 days after transplanting in an evaporative greenhouse (avg temp = 28–30 ◦C, 60–65 %RH), using deep water culture technique. Plants were grown in nutrient solution consisting of complete Hoagland’s solution (CTRL), and nutrient solutions lacking one of the following macronutrients and micronutrients: nitrogen (-N), phosphorus (-P), potassium (-K), iron (-Fe), manganese (-Mn), and copper (-Cu). The deficiency symptoms, growth patterns, and stress response mechanism were followed. All treatments except for the CTRL induced deficiency symptoms and physiological changes. Macronutrient deprivation reduced growth determined by the morphological parameters while micronutrient omission had no effect except for no iron treatment. The result showed that potassium and iron deficiencies had foremost adversely effect on growth of Japanese mint. Under nutrient stress conditions, plant only gave antioxidative responses to phosphorus and potassium deficiencies. However, the negative plant-stress relationship was found for no iron treatment indicating the detoxification mode of plant for lacking of micronutrient.